Strategic investment acquisitions performance in UK firms: the impact of managerial overconfidence. Issue 1 (11th March 2019) - Adel, Nour; Alkaraan, Fadi
Abstract : Purpose: This paper focuses on the influence of overconfident managers on strategic investment acquisitions performance, by investigating the influence of key contextual factors on acquirers' returns of UK domestic and cross-border acquisitions during the period 2000-2009. In this study, particular attention has been paid to management attributes (frequent acquirers vs non-frequent acquirers); method of payment (cash vs non-cash deals); the geographic scope (domestic vs cross-border deals); the type of the target (public vs private); the industry scope; and the relative size. Design/methodology/approach: An event study is used to analyse domestic and cross-border acquisitions. The market model is used for estimating the acquirers' abnormal returns of 1, 133 domestic and cross-border acquisitions by UK firms between 1 January 2000 and 31 December 2009. Findings: The findings reveal that acquirers with domestic targets have higher returns than cross-border targets. Infrequent acquirers generate higher returns from domestic and cross-border acquisitions than frequent acquirers. Further, acquirers that acquire domestic targets from different industrial sectors produce higher returns than acquirers with targets from the same sector. Acquirers with cash deals, private targets and high book-to-market ratio generate significant returns compared to acquirers with non-cash deals, low book-to-market ratio and public targets and that for domestic and cross-border deals. These results suggest that UK domestic and cross-border acquisitions are partially shaped by overconfident managers. Research limitations/implications: The study has a number of limitations, including the use of the market model, the data-collection process and the limited number of contextual factors. Future research may examine a number of avenues related to the current study, including incorporating the acquiring firms' financial characteristics. Practical implications: The study provides a better understanding of the influence of contextual factors on the success and failure of strategic investment projects such as acquisitions. Results of post-acquisitions performance in UK firms show how estimation of value can be distracted at the pre-acquisition stage because of overconfident managers. Originality/value: Results of post-acquisitions performance in UK firms show how estimation of value can be distracted at the pre-acquisition stage because of overconfident managers.